2017
DOI: 10.3892/etm.2017.5293
|View full text |Cite
|
Sign up to set email alerts
|

Formononetin ameliorates mast cell‑mediated allergic inflammation via inhibition of histamine release and production of pro‑inflammatory cytokines

Abstract: Abstract. Various allergic diseases cause allergic inflammation, which is mediated by mast cells. The current study investigated the anti-allergic inflammatory effects of formononetin and its mechanism of action in vitro using mast cells. Levels of histamine and pro-inflammatory cytokines, including tumor necrosis factor-α (TNF-α), interleukin (IL)-1β and IL-6, were measured to assess the effects of formononetin on allergic inflammation. The activation of intracellular calcium and nuclear factor (NF)-κB, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Moreover, elaeocarpusin from Elaeocarpus sylvestris significantly decreased TNF‐α and IL‐4 production via suppression of NF‐κB activation in mast cells (Kim et al, ). Besides, the suppressive effect of formononetin on NF‐κB activation also contributed to the attenuation of IL‐1β, IL‐6, and TNF‐α production (Xu & An, ). Hence, the suppressive effect of myricetin on IL‐4 and TNF‐α production was suggested due to inactivation of NF‐κB.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, elaeocarpusin from Elaeocarpus sylvestris significantly decreased TNF‐α and IL‐4 production via suppression of NF‐κB activation in mast cells (Kim et al, ). Besides, the suppressive effect of formononetin on NF‐κB activation also contributed to the attenuation of IL‐1β, IL‐6, and TNF‐α production (Xu & An, ). Hence, the suppressive effect of myricetin on IL‐4 and TNF‐α production was suggested due to inactivation of NF‐κB.…”
Section: Resultsmentioning
confidence: 99%
“…For example, an interesting study reported the effectiveness of lupeol for treating or reducing inflammation in a rat arthritis model (Geetha and Varalakshmi 2001). Formonetine in cell cultures has demonstrated potent anti-inflammatory properties, due to its ability to reduce the release of histamine (Xu and An 2017). In addition, anti-inflammatory and antinociceptive effects are reported for isoliquirititigenin and liquirititigenin (Kim et al.…”
Section: Discussionmentioning
confidence: 99%
“…FMT has a bioavailability of 21.8% and shows different absorption in all gastrointestinal segments ( Luo et al., 2018 ). An increasing body of evidence suggests that FMT exerts notable anti-inflammatory, anti-allergic, antioxidant, anti-hepatic steatosis, antiproliferative, and anticancer effects in vitro and animal models of many disease ( Wang et al., 2012 ; Xu and An, 2017 ; Fei et al., 2018 ; Li et al., 2018 ; Ong et al., 2019 ; Wang X. S. et al., 2019 ). Some reports demonstrate that FMT has neuroprotective effect in LPS-stimulated BV2 microglia and high-fat diet-induced cognitive disorder mice ( El-Bakoush and Olajide, 2018 ; Fu et al., 2019 ; Wang Y. et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%